Analyzing Distributed Deep Neural Network Deployment on Edge and Cloud Nodes in IoT Systems - Svorobej, Sergej; Ashouri, Majid; Lorig, Fabian; Davidsson, Paul; Spalazzese, Romina (IEEE, 2020)
For the efficient execution of Deep Neural Networks (DNN) in the Internet of Things, computation tasks can be distributed and deployed on edge nodes. In contrast to deploying all computation to the cloud, the use of Distributed DNN (DDNN) often results in a reduced amount of data that is sent through the network and thus might increase the overall performance of the system. However, finding an appropriate deployment scenario is often a complex task and requires considering several criteria. In this paper, we introduce a multi-criteria decision-making method based on the Analytical Hierarchy Process for the comparison and selection of deployment alternatives. We use the RECAP simulation framework to model and simulate DDNN deployments on different scales to provide a comprehensive assessment of deployments to system designers. In a case study, we apply the method to a smart city scenario where different distributions and deployments of a DNN are analyzed and compared.
IEEE International Conference on Edge Computing (EDGE)
Keywords: Edge Computing; Internet of Things; Distributed Deep Neural Networks; Simulation; Smart Cities; Telecommunications